2021
DOI: 10.1016/j.aninu.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Milk selenium content and speciation in response to supranutritional selenium yeast supplementation in cows

Abstract: The effects of selenium (Se) yeast supplementation on performance, blood biochemical and antioxidant parameters, and milk Se content and speciation were evaluated. Thirty-six mid-lactation Holstein dairy cows were randomly assigned to 1 of 3 treatments: 1) control (basal diet containing Se at 0.11 mg/kg DM), 2) basal diet + 0.5 mg supplemental Se/kg DM (SY-0.5), and 3) basal diet + 5 mg supplemental Se/kg DM (SY-5). Selenium was supplemented as Se yeast. The trial consisted of a 1-week pretrial period and an 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…In addition, this study found that the GSH-Px activity of chicken breast in the yeast-selenium-supplemented diet groups were significantly higher than that in the control group during postmortem aging, and there was a dose-effect. These results are supported by the previous study that showed selenium yeast significantly improved the antioxidant capacity of dairy cows, as shown in the significant increase in serum GSH-Px activity and total antioxidant capacity, which is similar to the results of this study ( Sun et al, 2021 ). This is because selenium is the active component of GSH-Px, and selenium yeast feeding enhances the activity of GSH-Px by enhancing the enrichment of selenium in chicken after slaughter ( Rotruck et al, 1973 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this study found that the GSH-Px activity of chicken breast in the yeast-selenium-supplemented diet groups were significantly higher than that in the control group during postmortem aging, and there was a dose-effect. These results are supported by the previous study that showed selenium yeast significantly improved the antioxidant capacity of dairy cows, as shown in the significant increase in serum GSH-Px activity and total antioxidant capacity, which is similar to the results of this study ( Sun et al, 2021 ). This is because selenium is the active component of GSH-Px, and selenium yeast feeding enhances the activity of GSH-Px by enhancing the enrichment of selenium in chicken after slaughter ( Rotruck et al, 1973 ).…”
Section: Discussionsupporting
confidence: 92%
“…According to Wichtel et al (2004) a milk Se concentration of less than 9.6 μg l -1 represent observable Se deficiency for cows, and a milk Se concentration of greater than 21.8 μg l -1 represent adequacy, but also clearly higher concentrations have been suggested to improve human Se supply. Milk Se concentrations up to 300 µg l -1 (Walker et al 2010) and even close to 600 µg l -1 (Sun et al 2021) have been reported with supranutritional experimental Se dosages. How high should Se concentration in organic milk be: above minimum requirements for calves, like in conventional farming, or able to provide Se enriched milk for consumers in future?…”
Section: Introductionmentioning
confidence: 84%
“…It is absorbed in the small intestine via methionine pathway while SS is absorbed mainly by passive diffusion, and it must undergo a metabolic transformation before it can be assimilated (Weiss 2005, Arshad et al 2021. Furthermore, SY has been reported to result in higher SeMet concentration in milk compared with SS (Juniper et al 2006) and with increasing SY dosages to higher proportion of SeMet in total milk Se (Sun et al 2021). Recently, other novel SeMet containing feed additives have been introduced for conventional dairy farming and the potential of nano-Se has been discussed (Arshad et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have proven the vital role of Selenium and zinc in stimulating the secretion of the hormone prolactin and increasing milk production in quantity and quality in dairy farm animals (Enjalbert et al, 2006). Although there are few studies (Trinta et al, 2020) available on the effect of baking yeast treated with zinc and Selenium and comparing its effect on milk production with the use of yeast alone or of Selenium and zinc separately and independently, there are signs and hints in some studies, although they do not include female goats, that there is such a synergistic effect (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%